No Association between Metabolic Syndrome and Periodontitis in Korean Postmenopausal Women - Jeong-In Kim (MDPI AG, 2021)
This study aimed to determine the association between metabolic syndrome (MetS) and periodontitis in Korean postmenopausal women. The study selected 3320 menopause women (40–79-year-old) from those who participated in the seventh Korea National Health and Nutrition Survey (2016–2018). This association was determined using frequency and multiple logistic regression analyses. The prevalence of MetS in postmenopausal women was 33.2%, and among the MetS components, abdominal obesity showed a higher odds ratio of periodontitis by 1.36 (95% confidence interval (CI): 1.12–1.65; p < 0.05). The odds ratio for periodontitis was 1.34 times higher (95% CI: 1.12–1.60) in the MetS prevalence group with three or more MetS components (p < 0.05); however, after adjusting for demographic characteristics and health behavior variables, it was not statistically significant. Therefore, our results indicated that MetS has no association with periodontitis in postmenopausal women after adjusting for confounding variables.